دراسة تحليلية لواقع القطاع الصناعي السوري ومساهمته في الاقتصاد الوطني - الصايغ, كارول (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف هذا البحث إلى إلقاء الضوء على واقع القطاع الصناعي السوري من خلال دراسة مساهمته في الاقتصاد الوطني، حيث تحاول الباحثة الوقوف على حجم مساهمة القطاع الصناعي السوري في الاقتصاد الوطني وتحليل مساهمة قطاعيه العام والخاص من خلال أربعة مؤشرات رئيسية وهي: - المؤشر الأول: مساهمة القطاع الصناعي السوري في تكوين الإنتاج المحلي الإجمالي. - المؤشر الثاني: مساهمة القطاع الصناعي السوري في تكوين الناتج المحلي الإجمالي. - المؤشر الثالث: مساهمة القطاع الصناعي في تشغيل اليد العاملة. - المؤشر الرابع: مساهمة القطاع الصناعي في التصدير. وبالتالي الوصول إلى مجموعة من النتائج التي تبين واقع القطاع الصناعي ومساهمته في الاقتصاد الوطني، إلى جانب تقديم مجموعة من المقترحات التي من الممكن أن تساهم في تذليل الأسباب المؤدية لانخفاض أدائه بالشكل الذي يمكنه من تحقيق الأهداف المرجوة منه. This research aims to study the real aspects of the Syrian industrial sector through the study of its contribution to the national economy. A Study regarding the size of the industrial contribution to the national economy is presented in this paper, as well as the presenting of an analysis of the contribution of both the public and the private sectors through four key indicators, these are: - The first indicator : the contribution of the industrial sector to the formation of Syrian domestic production. - The second indicator : the contribution of the industrial sector to the formation of Syrian GDP (Gross Domestic Product). - The third indicator : the contribution of the industrial sector to the operation of the labor force. - The fourth indicator : the contribution of the industrial sector to the export. And thus it provides a set of results that reflect both the reality of the industrial sector and its contribution to the national economy. Moreover it provides a set of proposals that could contribute toward overcoming the causes of the sector's low performance, so it can achieve the desired objectives.